رأس المال الفكري و تأثيره على الأداء المالي في المصارف الليبية (Economic studies journal, 2019)
This study examines intellectual capital (IC) performance of Libyan banks during the period from 2004 to 2010, using value-added intellectual coefficient (VAIC) methodology, and investigates the impact of IC on financial performance. It identifies the IC components that may be the drivers of the traditional indicators of bank success. The results of the study showed that private banks are more concerned with the components of intellectual capital compared to commercial banks and specialized banks. The results also showed that there is a positive relationship between the components of the (VAIC) and the (ROA). The study recommended that Libyan banks should add a post or position to manage intellectual capital in their organizational structures to help structure relevant strategies and policies on how to obtain, utilize and develop the best resources required for intellectual capital.
Keywords: IC Performance; Financial Performance Indicators; Libyan Bank